Examining secondary school teachers’ in – service training through bachelor of education degrees block release part – time programme in Zimbabwe - Matorevhu, Alois (International Journal on Teaching and Learning Mathematics, 2023)
Similar to its influence on other spheres of life, globalisation is changing the teaching and learning context, causing universities to explore new curriculum formats that may offer better fit with diverse student learning needs. One such format in the intensive mode delivery (IMD) category is the block – release part – time degrees programme, which comprises conventional traditional approaches and open and distance learning aspects. This case study sought to find out if the Bachelor of Education (BED) Degrees block release part – time programme offered in Zimbabwe by University R at Teachers’ College M as a centre, was developing desired teacher competences. Through structured interviews, data were collected from teacher educators and in – service teachers / teacher candidates in the programme. Coding and data reduction cumulated into themes upon which interpretation was based. Findings show that the BED block release part – time programme is a viable option which equips in – service teachers with degree qualifications for effective secondary school teaching and learning. However participants raised concerns about lack of time for them to develop competences in using learner – centred strategies. Teacher educators’ modelling of application of learner – centred teaching and learning strategies and teaching and learning media were identified as empowering in developing desired competences for in – service teachers to facilitate learning of diverse learners. However, based on findings, it is recommended that textbooks, time and teaching and learning media which currently lack, should be made available in the block release part – time degrees programme at University R centres, to ensure that in – service teachers are fully prepared to facilitate learning, through learner – centred strategies.